2020
DOI: 10.1177/2151459320915328
|View full text |Cite
|
Sign up to set email alerts
|

Potential Opioid-Related Adverse Drug Events Are Associated With Decreased Revenue in Hip Replacement Surgery in the Older Population

Abstract: Introduction: Opioid-related adverse drug events (ORADEs) are an increasingly recognized complication associated with the common prescription of opioids after orthopedic surgery. In this study, we attempted to understand how potential ORADEs following hip replacement surgery in older patients affected hospital length of stay, hospital revenue, and their association with specific risk factors and clinically relevant diseases occurring during hospitalization. Methods: We conducted a retrospective study using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Older age and male gender were associated with a higher risk of experiencing all general ORADEs. Advanced age was a significant risk factor in all nine studies, 11‐13,20‐24,27 with most studies 11,12,20‐24 reporting that age of ≥65 years increased the odds of all general ORADEs by 1.1–2.3 times compared to those aged <65 years. Eight studies 11‐13,20‐24 identified male gender as a risk factor which would increase the odds of general ORADEs by 1.1–2.0 times compared to females.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Older age and male gender were associated with a higher risk of experiencing all general ORADEs. Advanced age was a significant risk factor in all nine studies, 11‐13,20‐24,27 with most studies 11,12,20‐24 reporting that age of ≥65 years increased the odds of all general ORADEs by 1.1–2.3 times compared to those aged <65 years. Eight studies 11‐13,20‐24 identified male gender as a risk factor which would increase the odds of general ORADEs by 1.1–2.0 times compared to females.…”
Section: Resultsmentioning
confidence: 94%
“…These studies compared patients who experienced ORADEs and patients who did not (control group). Of these, 13 studies 11‐13,20‐29 involved a total of 1,887,711 surgical patients, one study 30 involved 731,208 medical patients, and two studies 31,32 involved a total of 355 hospitalized patients without stating the specialty (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations